A very vexing murder - Andrew, Lucy (Andrew, Lucy. Harriet Smith investigates., 2026)
"A witty debut whodunit that reimagines Harriet Smith, the gullible sidekick of Jane Austen's Emma, as a spitfire con woman, hired to break off an engagement and uncover a murderer in the genteel village of Highbury"-- Provided by publisher.